2008
DOI: 10.1097/bpb.0b013e328311d4f8
|View full text |Cite
|
Sign up to set email alerts
|

Congenital pseudarthrosis of the fibula and valgus deformity of the ankle in young children

Abstract: Treatment of cases of congenital pseudarthrosis of the fibula presenting with severe or progressive valgus deformity in early childhood is challenging. The purpose of the study presented was to analyse the deforming mechanisms to get therapeutic recommendations for this condition. A 2.5-year-old child was treated by resection of pseudarthrosis and distal tibiofibular fusion (Langenskiold operation) with autogenous bone grafting, associated with subtalar arthroereisis: progressive correction of the deformity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Moreover, the rates of refracture, tibial malalignment, ankle stability, and ankle deformities are all improved with management of the associated CPF 9,16,18,21–23 . Fibular osteosynthesis with bone grafting poses a high risk of failure due to bone graft resorption 1,24,25 . Other reliable methods include tibiofibular synostosis procedures such as the classic Langenskiold 25 procedure or the cross-union concept introduced by Choi et al 26 and Paley, 13 which support the fibula by uniting it to the tibia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the rates of refracture, tibial malalignment, ankle stability, and ankle deformities are all improved with management of the associated CPF 9,16,18,21–23 . Fibular osteosynthesis with bone grafting poses a high risk of failure due to bone graft resorption 1,24,25 . Other reliable methods include tibiofibular synostosis procedures such as the classic Langenskiold 25 procedure or the cross-union concept introduced by Choi et al 26 and Paley, 13 which support the fibula by uniting it to the tibia.…”
Section: Discussionmentioning
confidence: 99%
“…The pathology and mechanism of deformity development are similar to those involved in congenital pseudarthrosis of the tibia (CPT) 2 . Although a less serious condition as compared with CPT, it still carries the possibility of progressive ankle deformities that are problematic to treat 1 . The combination of CPF and CPT is an entity that had been reported to be the most common type of CPF, 3 which was identified as the most severe type of CPF (type 4) by Dooley et al, 2 corresponding to type 5 in the Boyd classification of CPT 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6.1 ) (Edwards and Menelaus 1987 ;Yang and Lee 2002 ;Lampasi et al 2008 ). The most frequent reason for the foot being everted at birth is a congenital calcaneovalgus deformity which is a benign condition that resolves spontaneously.…”
Section: Introductionmentioning
confidence: 99%
“…10 CPF has been controversially treated in the literature; Dooley et al recommended distal tibiofibular fusion because of the risk of failed fibular osteosynthesis and progressive ankle valgus. 6,11 Contrarily, the study by Martus and Johnston 9 found no ankle valgus in their cases and recommended against fusion of the tibia and fibula. Consequently, CPF can lead to ankle valgus and instability in the weightbearing joint and joint osteoarthritis, 1,12 and for these reasons, many surgical techniques have been proposed.…”
mentioning
confidence: 98%